Lévy statistics and laser cooling : how rare events bring atoms to rest - Bardou, François, 1967- (Cambridge University Press, 2002)
A graduate-level book for researchers in atomic physics, quantum optics, and statistical physics, written by world leaders in the fields of laser cooling and light-atom interactions. They demonstrate how Lvy statistics can be applied to problems where Gaussian statistics are inadequate, using laser cooling of atoms as a case study.